On Making Manifest: Statements by Artists at the HISK - Arkesteijn, Roel (Ghent HISK, 2012)
The role of the manifesto in the life and work of artists has changed dramatically over the years, from proclamation to whisper, proscription to question. In these artist texts, the question of what the 'manifesto' form can be or offer in the contemporary art landscape is approached in myriad ways, questioned, and reinvented. 'On Making Manifest' brings together texts from eighteen artists in residence at the Higher Institute for Fine Arts in 2012. The project, begun as a conversation, quickly took on a life of its own, becoming not only an interesting collection of artists' words, but a document of a particular place and moment in the conversation which is contemporary art. Contributions by Clare Noonan, Meggy Rustamova, Sara Bjarland, Patrick Wokmeni, Jeroen Uyttendaele, Rebecca Armstrong, Ieva Epnere, Federico Acal, Katrin Kamrau, Conny Kuilboer, Erika Hock, Paulien Föllings, Hamza Halloubi, Andris Eglitis, Alice De Mont, Line Boogaerts, Odilon Pain, Joachim Coucke
Keywords: 21st Century (2001-2100); Esthetics; Ghent (Belgium)